Moroccan Banks Analysis Using CAMEL Model - Ferrouhi, El Mehdi (International Journal of Economics and Financial Issues, 2014)
The present paper analyzes the performance of major Moroccan financial institutions for the period 2001-2011 using CAMEL approach. The research aims to evaluate Moroccan financial institutions’ capital adequacy, asset quality, management, earnings and liquidity and then determine financial performance, operating soundness and regulatory compliance of Moroccan financial institutions. The application of CAMEL model to major Moroccan financial institutions for the period 2001 to 2011 allows us to obtain a ranking of banks. We applied debt equity ratio for the analyze of capital adequacy parameter, loan loss provisions to total loans for the analyze of assets quality parameter, return on equity for analyzing management quality parameter, return on assets to analyze earnings ability and deposits on total assets ratio to analyze liquidity ability. Keywords: CAMEL approach; financial institutions; Morocco JEL Classifications: G20; G21